Literacy on Our Minds: A Student-Inspired Symposium - Albers, Peggy; Cowan, Kay (Language Arts, 2006)
In the context of an imagined symposium, this article addresses the literacy practices of elementary students ranging from first through sixth grade. The arguments the students make throughout the symposium, as well as the practices they relate, are drawn from arts-based literacy research conducted by the two authors. The imagined symposium begins with a joint keynote presented by two international literacy and art education scholars, Dr. Jerome Harste, and Dr. Elliott Eisner. With students as presenters in three breakout sessions that follow, they describe a learning environment in which they develop positive dispositions towards writing, how the arts support effective writing, and how to become a good writer. The students are joined in each of these sessions by discussants, literacy scholars whose work has emphasized the same topics addressed by the students. Collectively, the student presenters, the keynote speakers, and the discussants argue that the arts, as an alternative means of expression, position the learner to connect to affect, to refine meaning, and to reason metaphorically. (Contains 7 figures.)
Keywords: compétences; création; enseignement des arts; enseignement primaire; interdisciplinary approach; intermediate grades; lecture; literacy; student attitudes; writing Instruction

Semiotic Representations: Building Complex Literacy Practices through the Arts - Cowan, Kay; Albers, Peggy (Reading Teacher, 2006)
Learning to write well often proves to be one of the most difficult areas in the English language arts for young children. However, in these fourth- and fifth-grade language arts classrooms, children are offered opportunities to explore, think through, and express meaning across and within sign systems--in particular, using art, drama, and language. Children engage in arts- and language-based lessons and develop semiotic texts that are richly complex and imaginatively descriptive. Within the teacher's semiotic approach to literacy instruction, children develop habits in strategy use and knowledge of and practice in sign systems, both of which help them develop strong literacy practices. Once such experiences become habits of mind, students develop new insights into their own writing, creating, and talking about their texts, as well as the composing process. (Contains 9 figures.)
Keywords: arts; enseignement des arts; grade 4; grade 5; literacy; poésie; sémiotique; théâtre